Development of cost-efficient UHPC with local materials in Colombia (2020)
Ultra-high-performance concrete (UHPC) is an essential innovation in concrete research of recent decades. However, because of the high contents of cement and silica fume used, the cost and environmental impact of UHPC is considerably higher than conventional concrete. The use of industrial by-products as supplementary cementitious materials, in the case of recycled glass powder and fluid catalytic cracking catalyst residue (FCC), electric arc slag furnace (EASF), fly ash (FA), ground granulated blast slag furnace (GGBSF), rice husk ash (RHA) as partial substitution of cement and silica fume allows to create a more ecological and cost-efficient UHPC. Moreover, other products like limestone powder could be added to the mixture to reduce the final cost of UHPC and improve its rheology. For the 22 UHPC families with different binder composition tested, the design of the concrete mixtures was based on the goal of achieving mechanical and rheological properties with minimum amounts of cement, and a maximum amount of silica fume of 100 kg/m3, through a 3-factor Design of Experiments (DoE). The factors considered in this research were cement content in kg/m3 (factor A), water to binder ratio (factor B), and volume of superplasticizer (Factor C). Statistical tools such as Pareto plots, Principal Effect Plot, Stepwise Backward, Quadratic-order Regression, and Response Surface Methodology (RSM) were used to find the models for mechanical and rheological properties which included compressive strength at 1, 7, and 28-day, slump flow. Models for 28-day compressive strength and slump flow were the starting point for multi-objective optimization. The use of 590 kg/m3 of ASTM Type III cement, blended with micro limestone powder and recycled glass flour should be considered the most appropriate dosage to be employed in UHPC mixtures to reach a 28-day compressive strength over 150 MPa with a proper spread flow.